Prevention of Blackhole Attack Using Reactive AOMDV - E. Ahila Devi, E. Anna Devi, A. Ajoe Sweetlin Jeena (International Journal of Advanced Science and Technology, 2020)
Due to the rapid development of wireless sensor devices in terms of low power and inexpensive data‐relaying has been partially achieved because of the rapid progress in integrated circuits and radio transceiver designs and device technology. Because of this, the wireless sensor devices are able to gather information, process them if required and send them to the next sensor device. The resource constrained ad hoc wireless sensor network is versatile yet vulnerable to attacks. The communication infrastructure with less sensor networks may interact with the sensitive data in the hostile environment where the nodes may fail and new nodes may join the network, which may leads to the susceptibility to many kinds of security attacks. An adversary can eavesdrop on all the messages within the emission area, by operating in promiscuous mode. So, it is imperative that the protection of the network routing from the adversaries for the wireless ad hoc sensor network must be adopted for critical missions. A particularly devastating attack, predominant in today’s world is the wormhole attack. In this paper, the wormhole attack made by the malicious attacker in sensor networks has been implemented and also the number of Guard nodes required has been decided and implemented. Functions of the guard nodes like local inter-node collaborative data fusion and decision fusion to detect, isolate and prevent any further attacks is to be implemented. Simulations have been performed under different scenarios and from the results of simulation we have observed that our scheme is capable of improving the security in resource constrained wireless sensor networks.